Analytical evaluation of TPM performance based on an economic criterion. Issue 2 (3rd November 2020) - Chaabane, Kenza; Schutz, Jérémie; Dellagi, Sofiene; Trabelsi, Wajdi
Abstract : Purpose: Total productive maintenance (TPM) has been widely recognized as a strategic weapon for improving manufacturing performance. Evaluate efficiency of TPM implementation is considered as a key element in order to motivate staff and to give decision-makers more confidence. Design/methodology/approach: This study consists in developing a new method of evaluating TPM implementation, relying on analytical models and considering two preventive maintenance strategies: periodic and age-dependent. Findings: The preventive maintenance period and TPM period defined as decision variables are obtained simultaneously by maximizing the expected profit under TPM implementation. A numerical example is presented and a sensitivity study is developed to validate the proposed models. Originality/value: The aim of this research is to quantify, through analytic development, the impact of TPM implementation in a company by calculating and comparing the profit made with and without TPM.